Parental Child Abduction In Indonesia: A Criminal Law Perspective - Sofian, Ahmad; Yulia, Rena; Hendra, Rio; Setyawati, Melly; Capaldi, Mark P (Universitas Negeri Semarang, 2025)
This research examines parental conflicts that lead to